Analysis of Interleukin-4 in Thrombocytopenia Autoimmune Patients - Sitti Nurfaizah; Mansyur Arief; Uleng Bahrun (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2020)
Thrombocytopenia is a disease characterized by a decreased platelet count. Some of the causes are decreased platelet production, increased platelet use, such as due to infection, and autoimmune causes, namely the loss of tolerance of the immune system to self-antigens on the surface of the platelets and megakaryocytes marked with a platelet count <100,000 / μL and based on the pathomechanism classified as primary Immune Thrombocytopenia (ITP) and secondary, as well as several other causes. IL-4, one of the cytokines produced by Th2 which stimulates B cells to increase antibody production. The aim of this study was to compare IL-4 levels in primary ITP patients and non-primary ITP tombocytopenia. This study involved 30 primary ITP subjects and 30 non-ITP primary tombocytopenia subjects obtained based on data medical records, examination of IL-4 cytokine levels by the ELISA method. The results of this study that the IL-4 levels of the primary non ITP tombocytopenia subject group were higher than the primary ITP subject group, which means that there were differences in IL-4 levels in the primary ITP subject group and the non-ITP primary tombocytopenia subject group.